Impact of Phase Change Material (Butyl Stearate) and other insulation material on thermal performance of building envelope in different climates of India. (2021) - Hasan, Shaheen; Khan, Sabah; Uddin, Saif
Abstract: India is a developing country and thus has to cater to high energy demands in both rural and urban areas. Buildings and construction together account for 36% of global final energy use and 39% of energy-related carbon dioxide (CO2) emissions when upstream power generation is included. In India, the building sector consumes around 30% of the total energy. This research work is divided into two parts. The first one is the comparative evaluation of insulation materials for optimization of energy, and the other one is direct encapsulation of PCM material into the wall. The selection of building insulation materials such as EPS, XPS, PUF, GW and RW etc is based on market availability and suitability to weather conditions at building location. The Indian weather conditions have been classified into 6 different categories as per ISHRAE namely hot and dry, warm and humid, moderate, cold and cloudy, cold and sunny, and composite and similarly classified as Very Hot–Humid (1A), Dry (1B) as per ASHRAE 90.1 2007. Five locations of India with different climatic conditions have been chosen covering all Indian climatic zones which are Delhi (composite), Mumbai (Warm & Humid), Ahmedabad (Hot & Dry), Bangalore (Composite), and Srinagar (Cold). Selected types of insulation materials have been tested for thermal load performance of the building envelope in each of the above weather conditions including life cycle cost (LCC) analysis for 20 year period, carried out to select the best alternative amongst the selected insulation materials for each of the weather conditions. The parameters for the selection of insulation material are based not only on saving energy but also on protecting the environment from harmful gases. In Delhi state, The best suitable insulation material is RW since its payback is 1.08 years with maximum energy saving of 17.82%. In the case of Ahmedabad, GW gives maximum energy saving with optimum thickness, but the payback period is much lesser for Rock Wool viz., 1.06 years. In the case of Bangalore, the suitable material is RW with the payback period of 1.84 years. For Mumbai city, RW is the optimum material with a payback period of 2.02 years.